Control of biofilms using surfactants: persistence and regrowth - Simões, M. (2005)
The action of the cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS), respectively, a cationic and an anionic surfactant were investigated to control mature biofilms formed under turbulent and laminar flow, by P.fluorescens. The sanitizer action of the surfactants on biofilms was assessed by means of respiratory activity and variation of biofilm mass, immediately, 3, 7 and 12 h after the treatment of the chemicals. The latter experimental times were tested in order to assess the biofilm regrowth. The structure of the biofilms was assessed before and after surfactant treatment by SEM. The results showed that, laminar biofilms were more susceptible to the action of CTAB than those formed under turbulent flow. Concerning SDS, both biofilms showed analogous susceptibility to the surfactants. However, total inactivation of the cells within the biofilms was not achieved for both types of biofilms. CTAB application by itself did not promoted the detachment of biofilms from the surface. Regarding SDS, higher concentrations applied promoted significant biofilm inactivation. Turbulent and laminar flow had analogous susceptibility to SDS application. However, SDS did not promoted the detachment of biofilms from the metal surfaces. The structure of the biofilms was changed after the application of both surfactants. It was found that after CTAB and SDS application, the biofilms recovered its respiratory activity, reaching, in same situations, higher values than the ones found before chemical treatment. The CTAB application promoted similar recovery in the respiratory activity for both biofilms. Concerning biofilm behaviour after SDS treatment, turbulent biofilms showed a higher potential to recover their metabolic activity than laminar biofilms. Biofilm mass did not experienced any significant variation after the treatment, for both surfactants tested. This study highlights the need of care in choosing the correct procedure for biofilm control and the recalcitrant properties of biofilms.